Barth's theology and process theology - Welker, Michael (Theology today, 1986)
“In the following discussion, I will conduct a systematic comparison and ask: (1) What is common to Barth's and Whitehead's thought? (2) In the midst of these commonalities, what separates Barth's theology from Whitehead's theory? (3) How can Barth's theology and process theology mutually challenge and promote each other?”
Keywords: Begriff; Religion; Whitehead, Alfred North; Prozesstheologie; Theologie; Barth, Karl